LEGAL STATUS ON PURCHASE TRANSACTIONS BY MINORS IN BANDA CITY: AN ISLAMIC LAW PERSPECTIVE - Mufid; Mutiara Fahmi (JURISTA: Jurnal Hukum dan Keadilan, 2024)
The phenomenon of minors involved in buying and selling transactions in Banda Aceh City is a complex issue influenced by economic, educational, socio-cultural factors, as well as weaknesses in regulation and law enforcement. This research aims to analyze the factors causing this phenomenon and view it from the perspective of Islamic law and Law No. 13 of 2003 concerning Manpower. In Islamic law, a child who has not reached the age of maturity is considered not qualified to engage in valid transactions without the supervision of a guardian. Meanwhile, labor regulations in Indonesia prohibit minors from working except under certain conditions. This study uses a qualitative approach with a descriptive-analytical research type. Data were obtained through observation, interviews, and documentation methods, supported by secondary data from the literature. The research results show that poverty, low parental education, social norms, and the impact of the COVID-19 pandemic are dominant factors driving children to work in the informal sector. In Islamic law, small transactions conducted by children are considered valid if they meet the principles of justice and basic needs without exploitation. However, high-value transactions require guardian supervision to ensure validity. This research recommends the need for strict supervision, community education, and consistent law enforcement to protect children's rights in accordance with Islamic law and legislation.